The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1084/jem.20160061
|View full text |Cite
|
Sign up to set email alerts
|

GPR91 senses extracellular succinate released from inflammatory macrophages and exacerbates rheumatoid arthritis

Abstract: Littlewood-Evans et al. demonstrate that extracellular succinate leads to the propagation of inflammatory macrophage activation, providing translational evidence to support the development of GPR91 antagonists for the treatment of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
334
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(373 citation statements)
references
References 29 publications
(43 reference statements)
10
334
3
3
Order By: Relevance
“…C-AR reduced succinate accumulation by attenuating synovial hypoxia and then inhibited inflammation and fibrosis by preventing NLRP3 inflammasome activation. Consistent with the published studies which show that succinate accumulated in the synovial fluids from RA patients (32, 33), the finding of the role of succinate/NLRP3 inflammation signaling not only provides insight into the connection between inflammation and fibroblast activation but also reveals therapeutic targets for RA treatment. Moreover, our work presented a potential therapeutic strategy for the application of C-AR in the management of RA.…”
Section: Discussionsupporting
confidence: 86%
“…C-AR reduced succinate accumulation by attenuating synovial hypoxia and then inhibited inflammation and fibrosis by preventing NLRP3 inflammasome activation. Consistent with the published studies which show that succinate accumulated in the synovial fluids from RA patients (32, 33), the finding of the role of succinate/NLRP3 inflammation signaling not only provides insight into the connection between inflammation and fibroblast activation but also reveals therapeutic targets for RA treatment. Moreover, our work presented a potential therapeutic strategy for the application of C-AR in the management of RA.…”
Section: Discussionsupporting
confidence: 86%
“…It is tempting to speculate that accumulation of extracellular itaconate, which may occur following macrophage death, could provide an amplification signal to enhance the inflammatory activity of local macrophages. Indeed, a recent study has found that succinate release into the extracellular fluid in a model of antigen-induced arthritis can increase macrophage production of IL-␤, in a GPR91-dependent manner (12).…”
Section: Resultsmentioning
confidence: 99%
“…Reflective of the hypermetabolic status of RA Mø, glutamate is enriched in arthritic joints and stimulation of glutamate receptors regulates IL-6 release [60]. Similarly, succinate has been identified as a highly pro-inflammatory mediator [61,62]. GPR91-expressing Mø sense the succinate content in their environment, which triggers inflammasome activation and thus serves as an inflammatory amplification loop.…”
Section: Ra Macrophages – Glucose-intoxicated Hyperinflammatory Effementioning
confidence: 99%